1979
DOI: 10.1002/ar.1091930406
|View full text |Cite
|
Sign up to set email alerts
|

The cellular pattern of corpus luteal growth during pregnancy in the rat

Abstract: The cellular pattern of corpus luteal (CL) growth was studied in rats a t Days 6, 10, 12, 14, 16, 17 and 22 of pregnancy: term is Day 23. Measurements were taken of the percentage of the CL occupied by luteal cells, connective tissue and vascular space, luteal cell and nuclear volumes, and the number of luteal and endothelial cells in each of three CL in both ovaries of five rats a t each stage of pregnancy. Total CL volume increased from 1.08-3.23 pl over Days 10-17. This was mainly due to an increase in lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
3
29
0
1
Order By: Relevance
“…This is however unlikely, since the same effect is observed in rather thick sections (5 pm), and furthermore, this heterogeneity re lates relatively well with the variation in the function of these cells [3]. Indeed, in our study, the amount of relaxin variabilities during pregnancy correlated well with the evolution of the size of the cell and of the nucleus [6], Furthermore, in rat luteal cells during preg nancy, a nuclear increase is also associated with the increase in cytoplasm and the metabolic activity [14].…”
Section: Discussionsupporting
confidence: 87%
“…This is however unlikely, since the same effect is observed in rather thick sections (5 pm), and furthermore, this heterogeneity re lates relatively well with the variation in the function of these cells [3]. Indeed, in our study, the amount of relaxin variabilities during pregnancy correlated well with the evolution of the size of the cell and of the nucleus [6], Furthermore, in rat luteal cells during preg nancy, a nuclear increase is also associated with the increase in cytoplasm and the metabolic activity [14].…”
Section: Discussionsupporting
confidence: 87%
“…Meyer and Bruce [5] have observed that the increase in nuclear volume, particularly around mid-pregnancy, was correlated with an increased progesterone synthesis. The fact that we observed the same evolution of the nuclear size for the CL of type I, but not for the other types, suggests that the func tional activity varies from one type of CL to another.…”
Section: Discussionmentioning
confidence: 98%
“…During the estrous cycle in mice, an in crease of CL volume has been observed at metestrous for some newly formed CL and at diestrous 2 for degenerating CL [7], In the rat during pregnancy, CL volume increases 3 times between DIO and 17 [5], 6 times be tween D1 and 15 [2] and 2.6 times between D8 and 16 [3], In the mouse during pregnan cy, the maximum diameter of CL has been observed at D18 [9] and at D14 [11], In our study, a 10-fold increase has been observed between DO and 18.5 for CL volume of type I. This observation suggests a strong rela tionship between pregnancy and ovarian lu teal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations